1967
DOI: 10.1139/m67-165
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activities During the Asexual Cycle of Neurospora Crassa: I. Succinic Dehydrogenase

Abstract: Separate extracts of I\ier~orospora crassa grown either in Vogel's medium N, medium N + glutamate, or medium N which had bee11 made deficient in zinc, were assayed for succinic dehydrogenase ancl soluble protein a t intervals throughout the asesunl cycle. Succinic dehydrogenase, although apparently unnecessary for either the formation of conidia or coniclial germination, does appear to be necessary for rnycelial growth and for the production of conidiophores. Differences in the amount of enzyme during morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1968
1968
1972
1972

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These studies suggest that succinic dehydrogenase is present throughout germination and mycelial growth. A more recent report (13), however, indicates that succinic dehydrogenase was not necessary for germination; the enzyme was measurable in the ungerminated conidia, but not during the first 3 hr of conidial germination. It has also been reported that nicotinamide adenine dinucleotidase (NADase) was associated with the formation of conidia (3,20).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These studies suggest that succinic dehydrogenase is present throughout germination and mycelial growth. A more recent report (13), however, indicates that succinic dehydrogenase was not necessary for germination; the enzyme was measurable in the ungerminated conidia, but not during the first 3 hr of conidial germination. It has also been reported that nicotinamide adenine dinucleotidase (NADase) was associated with the formation of conidia (3,20).…”
Section: Introductionmentioning
confidence: 75%
“…The method of phasing the asexual cycle during development which permits sampling of cells at any time (13) was used during this study. The total units per culture and specific activities of nicotinamide adenine diphosphate-dependent glutamic dehydrogenase (NAD enzyme), nicotinamide adenine triphosphate-dependent glutamic dehydrogenase (NADP enzyme), NADase, and soluble protein were determined throughout the asexual cell cycle, from germination of conidia, through growth of mycelia, production of conidiophores, and the conidiophores' differentiation into new conidia.…”
Section: Introductionmentioning
confidence: 99%
“…Basal media and growth conditions were essentially those described by Gleason (6). For catabolite inductionrepression studies, cultures were grown on a New Brunswick incubator shaker at 20 C and 120 rpm in 500 After growth for 7 days, the media were further supplemented with the same quantities of carbon sources, and the mycelia were allowed to continue growth for 24 hr, then harvested over a nylon mesh filter, rinsed with glass-distilled water and frozen at -20 C until homogenized. For purification of the enzyme, cultures were grown in 2-liter Erlenmyer flasks in a medium containing glutamate as above with the exception that 1 g/liter yeast extract was added to improve the growth rate.…”
Section: Methodsmentioning
confidence: 99%
“…In the purification procedure it was found that the extract, with glutamate dehydrogenase specific activity of about 0.4, could be fractionated by adding (NH4)2SO to 40% saturation, sedimenting out the precipitate, adding (NH4).S04 to the supernatant (containing GDH') to bring it to 50% saturation, and sedimenting out the second precipitate which contained the GDH and which was then redissolved in solution A. This solution was dialyzed against 100 volumes of solution A for 24 …”
Section: Methodsmentioning
confidence: 99%